2017
DOI: 10.4274/tjcd.38278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of the Platelet-to-Lymphocyte Ratio for Diagnosing Complicated Acute Appendicitis

Abstract: Amaç: Akut apandisit (AA) dünyada en yaygın gözüken acil cerrahi hastalıktır. Preoperatif olarak bakılan ileri radyolojik görüntüleme yöntemlerine rağmen, komplike olguların değerlendirilmesi hala önemli bir sorun teşkil etmektedir. Bu çalışmada, platelet-lenfosit oranının ve beyaz küre değerinin komplike ve komplike olmayan apandisit olgularının ayrımında klinik etkinliğini ortaya koymaya amaçladık. Yöntem: Acil servise akut karın bulgularıyla başvurup AA ön tanısıyla acil laparotomi yapılan hastalar çalışmay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…High NLR and PLR values were shown to be associated with complicated abdominal infections and worse outcomes. [9][10][11][12] Debate is currently ongoing about the utility of NLR and PLR as inflammatory markers in diverticulitis. Of particular interest are associations with disease severity and clinical outcomes, and with the need for urgent interventions including surgery or CT-guided drainage of abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High NLR and PLR values were shown to be associated with complicated abdominal infections and worse outcomes. [9][10][11][12] Debate is currently ongoing about the utility of NLR and PLR as inflammatory markers in diverticulitis. Of particular interest are associations with disease severity and clinical outcomes, and with the need for urgent interventions including surgery or CT-guided drainage of abscess.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of NLR and PLR as prognostic markers in various malignant 4–6 and benign 7,8 conditions. High NLR and PLR values were shown to be associated with complicated abdominal infections and worse outcomes 9–12 . Debate is currently ongoing about the utility of NLR and PLR as inflammatory markers in diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of cytokines is increased at the beginning of inflammation in platelets like neutrophils, and increased cytokines contribute to the increase of inflammation by increasing the synthesis of new neutrophils and platelets. PLR has been used to evaluate the inflammatory process leading to the release of pro-inflammatory cytokines and the proliferation of megakaryocytes [19]. In a study published by Bekdas et al [20], the sensitivity was 61.8% and specificity was 62.5% for PLR in the differentiation of simple versus complex appendicitis in children.…”
Section: Discussionmentioning
confidence: 99%
“…The response to conditions such as trauma, infection, and inflammation is an increase in neutrophils and thrombocytes and a decrease in lymphocytes. The NLR and PLR have recently been used as indicators of inflammation in many areas [24][25][26][27][28][29][30]. Thus, this study was planned by considering that the leukocytes, leukocyte subsets, platelets, NLR, and PLR may guide the detection of diaphragmatic injuries.…”
Section: Discussionmentioning
confidence: 99%